2010
DOI: 10.1103/physreva.81.012709
|View full text |Cite
|
Sign up to set email alerts
|

Cross sections for electron scattering by carbon disulfide in the low- and intermediate-energy range

Abstract: In this work, we report a theoretical study on e − -CS 2 collisions in the low-and intermediate-energy ranges. Elastic differential, integral, and momentum-transfer cross sections, as well as grand total (elastic + inelastic) and absorption cross sections, are reported in the 1-1000 eV range. A recently proposed complex optical potential composed of static, exchange, and correlation-polarization plus absorption contributions is used to describe the electron-molecule interaction. The Schwinger variational itera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Using the SQFSM, whereas the calculated dσ d , ICS, and MTCS for elastic electron-molecule scattering do not change significantly from those calculated using the QFSM3, the calculated TCS and TACS are substantially affected. In fact, for a variety of atomic and molecular targets [25][26][27], the agreement of TCS and TACS obtained using SQFSM and the corresponding experimental values is significantly improved. Recently, a benchmark study by Staszewska et al [28] confirmed that the use of the introduced scaling factor can improve the reliability of the calculated cross sections for electron-atom collisions.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Using the SQFSM, whereas the calculated dσ d , ICS, and MTCS for elastic electron-molecule scattering do not change significantly from those calculated using the QFSM3, the calculated TCS and TACS are substantially affected. In fact, for a variety of atomic and molecular targets [25][26][27], the agreement of TCS and TACS obtained using SQFSM and the corresponding experimental values is significantly improved. Recently, a benchmark study by Staszewska et al [28] confirmed that the use of the introduced scaling factor can improve the reliability of the calculated cross sections for electron-atom collisions.…”
Section: Introductionmentioning
confidence: 88%
“…Experimental absolute dσ d , ICS, and MTCS in the 40-to 500-eV range are also reported. In the present work, although the dynamics for electron-molecule interaction is represented by the same complex optical potential as in our previous studies [26,27], an improvement is introduced in the solution of the scattering equations: instead of using the distorted-wave approximation to obtain the contribution of the absorption effects, the Lippmann-Schwinger scattering equation with the complex potential is solved exactly via the Padé approximant technique. Experimentally, the relative-flow technique (RFT) [29] is used to obtain absolute dσ d .…”
Section: Introductionmentioning
confidence: 99%
“…Although the EDCS, EICS and MTCS for elastic electron-molecule scattering calculated using the SQFSM do not change significantly from those obtained using the QFSM3, the TCS and TACS are substantially affected. In fact, for a variety of atomic and molecular targets [32][33][34][35], the agreement of TCS and TACS obtained using the SQFSM and the corresponding experimental values is significantly improved. More recently, a benchmark study by Staszewska et al [36] confirmed that the use of the introduced scaling factor can improve the reliability of the calculated cross sections for electron-atom collisions.…”
Section: Introductionmentioning
confidence: 90%
“…Experimental absolute EDCS, EICS and MTCS in the 40-500 eV range are also reported. In this work, the dynamics for the electron-molecule interaction is represented by a complex optical potential [32][33][34], whereas the Lippmann-Schwinger (LS) scattering equation is solved exactly using the Padé approximant technique [35]. Experimentally, the relative-flow technique (RFT) [37] is used to obtain absolute EDCS.…”
Section: Introductionmentioning
confidence: 99%